2017
DOI: 10.1177/2168479016674041
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Study on the Use of, Preference for, and Perceived Reliability of Mass Media for Drug-Related Information Among the General Public in Sarawak

Abstract: Television can be an important and attractive choice of mass media in a quality use of medicines (QUM) campaign. The Internet can be used to disseminate drug-related information in urban areas, whereas radio can be used in a QUM campaign targeting the rural public.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Inappropriate practices of self-medication in developing countries have increased due to a lack of knowledge, inadequate medical information exposure, and confusing or unclear product labelling on different medicines [ 44 , 45 ]. Before using OTC medicine, reading the product label is the key to proper use, as it is taken without consulting a doctor.…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate practices of self-medication in developing countries have increased due to a lack of knowledge, inadequate medical information exposure, and confusing or unclear product labelling on different medicines [ 44 , 45 ]. Before using OTC medicine, reading the product label is the key to proper use, as it is taken without consulting a doctor.…”
Section: Discussionmentioning
confidence: 99%
“…Changing behavior is the ultimate and highest priority in any public health campaign, but most of the mass media will change knowledge and awareness more easily than behavior. [30] In a meta-analysis, Shen et al analyzed the results of 22 studies and concluded that EE messages had a significant small effect on persuasion (r = .12) with a slightly stronger effect on health knowledge that on attitudes, intention, and behaviors. This suggests that EE can be more effective in communication health-related information, especially in educating people about a variety of health issues than changing attitudes and behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…It is less cost‐effective to conduct activities at rural areas since it involves more logistic costs, in addition to a lesser number of potential participants. Amidst the scarcity of the resources, mass media especially the radio could be the best media channel since past study revealed that most of the rural folks in the state were most accessible to radio and perceived most credible sources in obtaining drug‐related information …”
Section: Discussionmentioning
confidence: 99%